Política criminal de hiperencarceramento e audiências de custódia: congruências e inflexões - Morais, Lisandra Chaves de Aquino (2021)
The custody hearing, object of this research, was instituted in Brazil by the National Council of Justice, based on the pressure of social movements and arises from the perspective of confronting the vertiginous incarceration of the country, having as one of its main objectives to reduce police violence and the practices of torture. However, it encounters obstacles and challenges in a terrain permeated with contradictions and ambiguities, considering that the current criminal policy is oriented towards hyperincarceration and repressive criminal and police practices. The objective of this research is to analyze the custody hearings in the metropolitan region of Natal-RN with regard to their objectives in terms of criminal policy and mass incarceration. The specific objectives are 1) Analyze the custody hearing as a possibility to reduce incarceration levels; 2) Analyze the custody hearing as an instrument that aims to reduce or curb torture, ill-treatment and police violence; 3) Problematize custody hearings as a resource to guarantee rights and reduce criminal practices within the scope of the penal system. It is a research with a dialectical historical materialist base that had as a methodological path the participation and observation of 20 custodial hearings in the metropolitan region of Natal, as well as the survey of data since its implementation until the present day. The results show that, in addition to maintaining prisons as a rule and underreporting practices of violence or torture, custody hearings continue to reproduce violations of procedural guarantees. That said, this research argues that the contradictions present in the implementation and execution of this instrument of penal guarantee are related to the very way in which the criminal issue is structured in the capitalist mode of production.